Enhanced ant colony system for reducing packet loss in wireless sensor network - Abdul Nasir, Husna Jamal; Ku-Mahamud, Ku Ruhana; Kamioka, Eiji (Science and Engineering Research Support Society, 2018)
Routing packets from source nodes to destination nodes in Wireless Sensor Network (WSN) is complicated due to the heterogeneous nature and distribution of sensor nodes. Packet loss problem in WSN may occur when the sensor node carrying more packets than its capacity. This can affect throughput, energy consumption and success rate of the WSN system. This paper proposes an improved Ant Colony Optimization (ACO) algorithm for packet routing to solve packet loss problem in wireless sensor network. The proposed algorithm is inspired from a variant of ACO which is Ant Colony System (ACS) that consists of local and global pheromone updates to enhance routing path exploration and exploitation. Experimental results showed that the proposed algorithm improved the performance of the proposed ACS algorithm in terms of reducing packet loss and increasing the energy efficiency of sensor nodes.